2021
DOI: 10.3390/su13179657
|View full text |Cite
|
Sign up to set email alerts
|

20 Years of Research on Real Estate Bubbles, Risk and Exuberance: A Bibliometric Analysis

Abstract: Since the 2008 global financial crisis, the study of real estate risks, bubbles and exuberance has attracted a lot of attention, which is of great significance to the government, enterprises and individuals. This paper carries out a statistical and bibliometric analysis of 739 studies over the past 20 years in this field, and identifies the theoretical basis, research topics and latest research hotspots in this field. Through the construction of a co-citation network and co-word network, we find that the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…While the 2008 crisis brought about renewed concerns in markets, global integration has not diminished, and associated risks remain latent (Li et al 2021). Since then, specialized literature has made significant advances in areas related to real estate phenomena, for which the use of bibliometric techniques is not new.…”
Section: Introductionmentioning
confidence: 99%
“…While the 2008 crisis brought about renewed concerns in markets, global integration has not diminished, and associated risks remain latent (Li et al 2021). Since then, specialized literature has made significant advances in areas related to real estate phenomena, for which the use of bibliometric techniques is not new.…”
Section: Introductionmentioning
confidence: 99%
“…Our paper will be based on the work byPhilip et al (2015), which provides econometric detection mechanisms for identifying the dates of the bubble. This piece of work is widely cited in housing bubble-related research, such as Bangura and Lee (2020),Li et al (2021),Andre et al (2022),Tang (2017) and others.Recently, a lot of attention has been paid to the effect of the COVID-19 pandemic on the economic and financial environment. For example,Ulku et al (2023) argued that COVID-19 formed a negative bubble in the stock market and led to substantial wealth transfers among investor types,Ji et al (2022) found that the global stock markets performed poorly during the pandemic,Gharib et al (2021) found that a bilateral contagion effect of bubbles in oil and gold markets during COVID-19,Ding et al (2022) studied how COVID-19 affects the corporate sector at different stages of COVID-19 outbreak, andChong et al (2020) proposed that "the slow growth, the sluggish recovery of trade and the cross-country transmission of the unemployment rate are three significant risk factors that ASEAN economies are faced with".…”
mentioning
confidence: 99%